1996
DOI: 10.3109/03005369609079043
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the binaural interaction component in the auditory brainstem response

Abstract: In humans, the binaural interaction at the brainstem level has been studied for over 15 years. The binaural interaction component (BIC) is obtained by subtracting the summed auditory brainstem response (ABR) in the monaural stimulus mode from the ABR obtained in the binaural stimulus mode. By nature of this subtraction process, the signal-to-noise ratio of the difference waveform is poor, requiring an objective detection criterion to decide whether a significant BIC is present. In this study, the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 13 publications
3
29
1
1
Order By: Relevance
“…Significant peaks in the binaural difference waveform have been demonstrated in most normal-hearing subjects once the averaging is based on a large number of stimulations [Jones and Van der Poel, 1990;Gunnarson and Finitzo, 1991;Levine and Davis, 1991;Stollman et al, 1996]. The present data are in agreement with those from previous studies, i.e.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Significant peaks in the binaural difference waveform have been demonstrated in most normal-hearing subjects once the averaging is based on a large number of stimulations [Jones and Van der Poel, 1990;Gunnarson and Finitzo, 1991;Levine and Davis, 1991;Stollman et al, 1996]. The present data are in agreement with those from previous studies, i.e.…”
Section: Discussionsupporting
confidence: 83%
“…At the brainstem level, investigation of the auditory brainstem response (ABR) has shown the binaurally evoked potentials to differ in amplitude from the sum of the two corresponding monaurally evoked potentials. Although a great deal of data is available on binaural interaction as reflected in human ABR [Hosford et al, 1979;Dobie and Norton, 1980;Decker and Howe, 1981;Levine, 1981;Wrege and Starr, 1981;Dobie, 1982;Kelly-Ballweber and Dobie, 1984;Dobie and Wilson, 1985;Furst et al, 1985;Fullerton et al, 1987;Fowler and Swanson, 1988;McPherson et al, 1989;Jones and Van der Poel, 1990;Gunnarson and Finitzo, 1991;Levine and Davis, 1991;McPherson and Starr, 1993;Parthasarathy and Moushegian, 1993;Lasky et al, 1995;McPherson and Starr, 1995;Stollman et al, 1996], few ABR studies have been focused on the effects of interaural time difference (ITD).…”
Section: Introductionmentioning
confidence: 99%
“…Results for the OME children were compara ble with normative data. The absence of (sig nificant) BIC peaks in normal-hearing sub jects has been mentioned before in the litera ture on binaural interaction [25,28]. We be lieve that, at present, the results are too vari able, even for normal-hearing adults, to be of clinical value.…”
Section: Suppression O F Oa Es With Contralateral Noise St Imulationcontrasting
confidence: 43%
“…For baseline-to-peak-measurements peaks with voltages V bp smaller than 3r BD (99.7% confidence level for Gaussian measurement errors) were not regarded as significant and hence were discarded. The 3r-criterion was proposed by Stollman et al (1996) and found to be superior to a template matching method for the detection of significant BD components. However, the measurement of the residual noise r, and therefore, the detection of significant BD components, is far more accurate in the present study since it relies on the analysis of single sweeps in contrast to the conventional methods relying on the comparison of two (sub-)averages or the variance in the averaged prestimulus interval Riedel et al, 2001).…”
Section: Discussionmentioning
confidence: 99%